2011
DOI: 10.1021/jz201259v
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Energy Transfer in Light-Harvesting Systems, III: The Influence of the Eighth Bacteriochlorophyll on the Dynamics and Efficiency in FMO

Abstract: The most recent crystal structure of the Fenna-Matthews-Olson (FMO) protein complex indicates that each subunit contains an additional eighth chromophore. It has been proposed that this extra site functions as a link between the chlorosome antenna complex and the remaining seven chromophores in FMO [Schmidt am Busch et al, J. Phys. Chem. Lett., 2, 93 (2011)]. Here, we investigate the implications of this scenario through numerical calculations with the generalized Bloch-Redfield (GBR) equation and the non-inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
223
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(237 citation statements)
references
References 40 publications
13
223
1
Order By: Relevance
“…1(c)) are found to lie close to the chlorosome baseplate, suggesting that initial electronic excitation occurs at one of these sites (or involves an excitonic state delocalised across these chromophores 42 ), while Bchl 3 is the energetic sink in the system, funnelling electronic excitation energy to the RC. While the exact mechanism of EET to Bchl 3 is somewhat ambiguous, in part because the initial excitation in the native environment is similarly ambiguous, recent experimental and theoretical work has shown that FMO exhibits at least two different pathways for EET to site 3; [5][6][7]42 as we show below, these multiple transport paths, as well as the inherent heterogeneity of connectivity between different Bchl sites, are important features in maintaining robust EET.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…1(c)) are found to lie close to the chlorosome baseplate, suggesting that initial electronic excitation occurs at one of these sites (or involves an excitonic state delocalised across these chromophores 42 ), while Bchl 3 is the energetic sink in the system, funnelling electronic excitation energy to the RC. While the exact mechanism of EET to Bchl 3 is somewhat ambiguous, in part because the initial excitation in the native environment is similarly ambiguous, recent experimental and theoretical work has shown that FMO exhibits at least two different pathways for EET to site 3; [5][6][7]42 as we show below, these multiple transport paths, as well as the inherent heterogeneity of connectivity between different Bchl sites, are important features in maintaining robust EET.…”
Section: Introductionmentioning
confidence: 83%
“…1 Much of the contemporary experimental and theoretical interest in photosynthetic PPCs has focussed on the role of quantum coherence in the mechanism and efficiency of EET. 1,[3][4][5][6][7][8][9][10][11][12] Time-resolved non-linear spectroscopic studies suggest the existence of long-lived quantum "beats" in the a) Electronic mail: S.Habershon@warwick.ac.uk population dynamics of PPCs demonstrating that quantummechanical effects may play a role in EET, 1,7,9,10,13 contrary to the textbook idea that such coherence should be "washed-out" by the thermal environment. In contrast, far less emphasis has been placed on answering a more fundamental question: why are PPCs built the way they are?…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations